2007
DOI: 10.1152/ajpregu.00329.2007
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of apolipoprotein AIV with cholecystokinin on the control of food intake

Abstract: Apolipoprotein AIV (apo AIV) and cholecystokinin (CCK) are peptides that act both peripherally and centrally to reduce food intake by decreasing meal size. The present study examined the effects of intraperitoneally administered bolus doses of recombinant apo AIV, CCK-8, and a combination of subthreshold doses of apo AIV and CCK on 4-h food intake in rats that were fasted overnight. Apo AIV at 100 μg/kg reduced food intake significantly relative to the saline control for 1 h, as did doses of CCK-8 at or above … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 39 publications
3
28
0
Order By: Relevance
“…Fujimoto et al ( 82 ) also provided evidence that the potential site of action of apoA-IV is in the central nervous system. Consistent with this, central or peripheral administration of recombinant apoA-IV reduces food intake without causing malaise ( 55,(83)(84)(85), while administration of apoA-I at comparable doses has no effect on satiation ( 55 ). The latter is an important control because apoA-1 and apoA-IV have related structures and comparable actions on some aspects of lipoprotein metabolism.…”
Section: Apoa-iv As a Satiety Factormentioning
confidence: 61%
See 1 more Smart Citation
“…Fujimoto et al ( 82 ) also provided evidence that the potential site of action of apoA-IV is in the central nervous system. Consistent with this, central or peripheral administration of recombinant apoA-IV reduces food intake without causing malaise ( 55,(83)(84)(85), while administration of apoA-I at comparable doses has no effect on satiation ( 55 ). The latter is an important control because apoA-1 and apoA-IV have related structures and comparable actions on some aspects of lipoprotein metabolism.…”
Section: Apoa-iv As a Satiety Factormentioning
confidence: 61%
“…Combinations of sub-threshold doses of CCK and apoA-IV produce a short-term satiation, and this satiation effect is attenuated by the CCK-1R antagonist, lorglumide ( 85 ). Combinations of higher doses of CCK and apoA-IV cause a prolonged satiating effect (up to 4 h) that is not seen by either alone.…”
Section: Apoa-iv As a Satiety Factormentioning
confidence: 95%
“…Apo AIV is an anorectic protein synthesized in the intestine and hypothalamus that reduces food intake (10,22,25). Mice with apo AIV deficiency (apo AIV KO mice) exhibit normal food intake and normal body weight during ad libitum feeding.…”
Section: Discussionmentioning
confidence: 99%
“…Both exogenous and endogenous CCK activate intestinal vagal afferent neurons via CCK1R to relay satiation signals to the brain (5,9,19). Previous data from our laboratory have demonstrated that coadministration of apo AIV and CCK-8 has an additive interaction in that a combination of subthreshold doses of apo AIV and CCK significantly reduces food intake relative to apo AIV or CCK-8 alone (25). The aims of the present study were to determine 1) whether CCK-8 alone can inhibit food intake when apo AIV is absent and 2) whether there is a change in the gene expression of CCK1R when apo AIV is absent.…”
mentioning
confidence: 90%
“…Thus, CCK must interact with other mechanisms to control eating. Synergistic interactions between CCK and several other negative-feedback signals have been identified, including orosensory nutrient stimuli [106], gastric volume [107], leptin [108], small-intestinal 5HT [109,110], apolipoprotein AIV [111], pancreatic glucagon [112], amylin [113], and insulin [7].…”
Section: Gastrointestinal Peptides and Satiation: Introductionmentioning
confidence: 99%